Innovative Testing Investigations on the Influence of Particle Morphology and Oil Contamination on the Geotechnical Properties of Sand - Siang, Alvin John L. M.; Wijeyesekera, Devapriya Chitral; S. Yahya, S. Muhammad Asyraf; Ramlan, Masrulaini (International Journal of Integrated Engineering, 2014)
Shear strength and the permeability in a soil mass are two prime parameters that characterize the geotechnical behaviour of the soil. These parameters (c', Ø’, k) help assess the bearing capacity and settlement characteristics of foundations, stability of slopes, lateral earth pressure on retaining walls and fluid infiltration. Geo environmental contamination resulting from chemicals and oil spills are becoming very common news and these  alter the inter-particle behaviour of the soil, making it to lose its strength and deformability considerably and also become less permeable. This study focuses on the effects of contamination of sands with different grading size and particle shapes on its shear strength and its coefficient of permeability. Well graded and gap graded sand samples were used in the research. A simple statistical approach was used to define not only the particle size but also its shape distribution. Comparison of the shear strength of these sand samples were tested in an automated motorised direct shear apparatus under both dry and fully saturated conditions (with water and also with oil). The coefficient of permeability of the two sands under clean and contaminated conditions was obtained using a modified falling head permeability test. It was observed that the well graded sand which was submerged in oil apparently had the lowest peak shear strength values. However, a higher order of cohesion was apparent when the soil was contaminated with oil. Permeability was also an issue, as by virtue of its viscosity, the oil hindered the water seepage through the sand samples when compared with clean sands. However, it appeared that with more viscous liquid contaminants, the rate of water infiltration was notably higher. Permeability was also affected by the particle grading and shape distribution. The significant loss in strength and the tortuosity of water flow in the soils can cause major problems such as unwarranted floods and potential failures in civil engineering works. Therefore, the extent of the problem that is caused by oil contamination needs to be truly understood to minimize unwarranted construction risk.